Urgensi Guidance dan Counseling terhadap Peningkatan Prestasi Belajar di Sekolah - Fatimah Umi Bukhari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
Every one must face up to the many problems in his life, this if is due to us to find the best solution to end these problems, so that they are able to solve it until they are to use the potencial within their self as good as possible and achieves it’s denefist and so that they may feed hous great mercies in their life. And like that in the world of education, guidance and counseling plays a crucial role in finding solution and solve the problem, cause are help the students to know them self and them present and possible future situation so that they can make use of characteristics and potentialiste is away that is both statisfying to them self and penaficial to society, and tuther can learn now to solve future problems and meet future needs.